2012
DOI: 10.4171/cmh/257
|View full text |Cite
|
Sign up to set email alerts
|

Current twisting and nonsingular matrices

Abstract: Abstract. We show that for k ≥ 3, given any matrix in GL(k, Z), there is a hyperbolic fully irreducible automorphism of the free group of rank k whose induced action on Z k is the given matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…The proposition follows from a slight modification of the arguments from Theorem 5.2 in [12]. In its proof (equation (5.9)), we showed that for for every ǫ > 0 and integer r > 0, there is an N > 0 such that for n ≥ N:…”
Section: Dehn Twistsmentioning
confidence: 96%
See 4 more Smart Citations
“…The proposition follows from a slight modification of the arguments from Theorem 5.2 in [12]. In its proof (equation (5.9)), we showed that for for every ǫ > 0 and integer r > 0, there is an N > 0 such that for n ≥ N:…”
Section: Dehn Twistsmentioning
confidence: 96%
“…These types of outer automorphisms were considered in [13] and used in [12] to show that there is no homological obstruction to full irreducibility. We briefly recall the setup here; for more details consult either of the references [12,13].…”
Section: Examplementioning
confidence: 99%
See 3 more Smart Citations